The Value of Work for Russian University Students: The Logic of Justifying the Choice in Favor of Personal Gain or Social Utility - Anita Poplavskaya (Journal of Economic Sociology, 2023)
This article is aimed at theoretical interpretation of the value concept in economy, reconsideration of the traditional dichotomy of work values as well as at providing the empirical evidence of this new approach validity. It is common to distinguish between internal work values, which are mainly described as an interest in the content of tasks and the autonomy of their performance, and external ones, associated with the desire to get high salaries and achieve other benefits, exogenous to the work itself. However, a broad theoretical analysis of the value concept in the labor sphere, supported by the overview of the monographs by economists D. Throsby, M. Mazzucato, anthropologist D. Graeber and the works of economic sociologists, appeals to focus on the dichotomy of opportunities for obtaining high earnings or social utility by the employee involvement in work as well as the problem of reverse causality between these characteristics of work under the conditions of modern capitalist economy. The data was collected in December 2021 and included 38 interviews with students and graduates of Russian universities aged 18–24 years. The empirical part begins with an analysis of the value conflict that arises while making choice between individually beneficial and socially useful areas of employment. The desire to pursue purely personal interests in the sphere of paid employment matches with the market logic of choosing a future profession, analysis of supply and demand in specific areas of employment, clear ideas about the desired level of income as well as expansive self-development strategies based on expert advice and including multiple employment, frequent change of employers and firms, desire to devote time to individual “operational activities” as a means to develop hard skills. Orientation towards social utility includes a setting for long-term and gradual self-development within the professional sphere, its conscious choice as a “vocation”, a nonpossessive attitude towards money received for work, an active desire to achieve higher levels of professional knowledge and skills as well as plans to acquire socially recognized status in the future. It was also revealed that the orientation towards social utility is justified by domestic logic, rooted in the system of parental or own family relations, and has a gender specificity. It was reflected in the author`s concept of the anchors of utilityoriented approach to work.